POST-INDUSTRIAL MOTIVATION POLEMICS BEHIND THE ISSUE OF CROSS-MEDIA PLASTIC BAGS DIET - Yesica Yuliani Clara; Laurencia Steffanie Mega Wijaya Kurniawati; Rustono Farady Marta; Aditya Kumar Shukla (Universitas Bunda Mulia, 2021)
Garbage is often an environmental problem, especially in Indonesia, which produces more than 100 tons of waste that is difficult to decompose. This fact creates a separate concern for the government both at home and abroad, especially in the maintenance of the environment and forestry. After socializing the minimization of plastic bags, other problems arise such as reduced employment opportunities due to lower levels of plastic bag consumption. This research reveals several viewpoints of domestic and foreign media that show the disadvantages of plastic factories since the government decree on reducing the use of plastic bags, and with media comparative research methods that will show the objectives of each media through news packaging with analysis of the language used.